Bovine herpesvirus 1 in the northeast of Algiers, Algeria: Seroprevalence and associated risk factors in dairy herd - Kaddour, Abdenour; Bouyoucef, Abdallah; Fernandez, Gonzalo; Prieto, Alberto; Geda, Fikremariam; Moula, Nassim (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The present study was conducted to estimate the seroprevalence and associated risk factors of bovine herpesvirus 1 (BoHV-1) in a dairy herd in the northeast of Algiers, Algeria. Materials and methods: The target area is in the northeast of Algiers with humid to semi-dry climate and known for its economically important production of cattle. A total of 1,066 randomly selected individual blood samples of dairy herd collected at 120 dairy farms from rural districts of northeast of Algiers were evaluated with antibodies against BoHV-1 using commercial enzyme-linked immunosorbent assay kits, to determine the BoHV-1 infection status of the herds. A questionnaire submitted to the farmers during collection of the blood samples was used to collect data on potential BoHV-1 associated risk factors. Results: In the present study, the estimated farm and individual animal BoHV-1 seroprevalence levels were 58.33% and 14.16%, respectively. A logistic regression analysis of the random-effects model revealed that the significant associated risk factors for the present farm and individual animal seroprevalence levels were rural district, cattle introduced to the farm, region, and hygiene. Conclusion: This study found higher seroprevalence of BoHV-1 in the northeast of Algiers. The results could be used in designing the prevention and control strategy of BoHV-1 in the northeastern part of Algeria. J. Adv. Vet. Anim. Res., 6(1): 60-65, March 2019